Moisture dynamics during Coniophora puteana brown rot degradation of Scots pine sapwood - Belt, Tiina; Treu, Andreas; Möttönen, Veikko; Altgen, Michael (Elsevier, 2026)
Wood has many attractive material qualities, but it is susceptible to biological degradation by wood-decaying fungi. Moisture is one of the critical requirements for wood decay, but much remains unknown about moisture dynamics in decaying wood. To fill this knowledge gap, this study investigated moisture in Scots pine sapwood during decay caused by the brown rot fungus Coniophora puteana. Samples were exposed to decay in two time-series experiments; mass loss and moisture content were recorded over the course of decay, and the bound and free water populations in the samples were analysed using low-field nuclear magnetic resonance (LFNMR) relaxometry in both the decaying state and at full water saturation. Selected samples were also used for water vapour sorption measurements. The time-series decay tests showed that moisture content initially increased due to fungal activity but decreased over time when corrected for mass loss, contrary to the general belief that moisture content increases with decay. LFNMR revealed that bound water content increased on a decayed-mass basis in the decaying state and at saturation, but no increase was seen after correction for mass loss. Free water content followed gravimetric moisture content in the decaying state, but the saturated state measurements revealed an initial increase and subsequent decrease with mass loss. Degradation caused changes in hygroscopicity, but our data show that overall moisture content is regulated by fungal activity rather than by material properties. These findings highlight the complexity of water interactions during fungal degradation, offering valuable new insights into wood degradation mechanisms.
Keywords: bound water; brown rot; decay; hygroscopicity; LFNMR; moisture content; sorption